Identification and Modeling of SI-LAUT: Information System for Indonesian Maritime Resources Using Penta-Helix Model - Istyanto, Noerma Pudji; Nasrullah, Muhammad; Fikri, Mohammad Anas (Universitas Bina Darma, 2024)
Indonesia, as a country predominantly surrounded by the sea, holds significant potential in marine resources, fisheries, and other maritime fields. However, there is still a lack of awareness and understanding among the Indonesian population regarding these maritime aspects. Currently, there are various media and information sources related to this topic, ranging from websites and applications to supporting information systems. Nevertheless, users often struggle to find and comprehend this information easily and comprehensively. Existing information systems tend to be fragmented or operate independently, leaving many laypeople unable to fully optimize the existing potential. To address this, researchers aim to identify and model a comprehensive and integrated information system focused on marine and other maritime resources, known as SI-LAUT The research method employed in this study consists of literature review, stakeholder identification based on the Penta-Helix model, analysis of the existing system, and gap analysis in comparison to previous research that focused on the implementation of other maritime and marine information systems. The results of this research consists of a recommendation for an information system development model that can assist various stakeholders based on the Penta-Helix Model. These stakeholders include government bodies, entrepreneurs, academics, as well as the general public or other communities. The goal is to optimize the management and utilization of Indonesia’s marine resources, ultimately positioning it as a global maritime powerhouse.